LINGUISTIC FEATURES OF CONCEPTUAL METAPHOR - Sagatova Muborak Payzidinovna (Web of Journals Publishing, 2024)
Conceptual metaphors are central to how we structure and communicate abstract thoughts and complex experiences. These metaphors do not merely involve figurative language but are rooted in the very way humans think. As George Lakoff and Mark Johnson (1980) argue in their seminal work Metaphors We Live By, metaphors are not just a matter of linguistic expression; they shape how we conceptualize the world. This article explores the linguistic features of conceptual metaphors, outlining how these metaphors are structured, realized in language, and function in communication.
Keywords: Conceptual metaphors, linguistic features, cognitive process, cognitive mappings, components, structural mapping, lexical choices, syntactic structure